SEGREGASI ETNO-RELIGIUS: UPAYA RESOLUSI KONFLIK DAN PEMBANGUNAN PERDAMAIAN - Mustain Mustain (LP2M - Universitas Islam Negeri (UIN) Walisongo, 2013)
Ethno-religious segregation in Lombok, especially in Mataram existed because of population migration and the implication of the implemenation of the policy on the politic of Karang Asem Hinduism Mataram Kingdom that dominated this area for more than one century (1670-1820). The policy subjected to the community made the fixed social stratification in the context of community settlement, and generated two different groups, the Balinesse-Hiduism as the noble and Sasak-Muslim as the lower-level society members. Applying qualitative method and conflict study approach it was revealed that historical legacy had been become the social-psychological barrier for the two communities for making open and trustful interaction.